Prognostic Value of Serum Magnesium in Mortality Risk among Patients on Hemodialysis: A Meta-Analysis of Observational Studies - Hongwei Wu; Qiang Li; Lijing Fan; Dewang Zeng; Xianggeng Chi; Baozhang Guan; Bo Hu; Yongping Lu; Chen Yun; Bernhard Krämer; Berthold Hocher; Fanna Liu; et al. (Karger Publishers, 2020)
Background: Previous studies have reported that serum magnesium (Mg) deficiency is involved in the development of heart failure, particularly in patients with end-stage kidney disease. The association between serum Mg levels and mortality risk in patients receiving hemodialysis is controversial. We aimed to estimate the prognostic value of serum Mg concentration on all-cause mortality and cardiovascular mortality in patients receiving hemodialysis. Methods: We did a systematic literature search in PubMed, EMBASE, Cochrane Library, and Web of Science to identify eligible studies that reported the prognostic value of serum Mg levels in mortality risk among patients on hemodialysis. We performed a meta-analysis by pooling and analyzing hazard ratios (HRs) and 95% confidence intervals (CIs). Results: We identified 13 observational studies with an overall sample of 42,967 hemodialysis patients. Higher all-cause mortality (adjusted HR 1.58 [95% CI: 1.31-1.91]) and higher cardiovascular mortality (adjusted HR 3.08 [95% CI: 1.27-7.50]) were found in patients with lower serum Mg levels after multivariable adjustment. There was marked heterogeneity (I2 = 79.6%, p < 0.001) that was partly explained by differences in age stratification and study area. In addition, subgroup analysis showed that a serum Mg concentration of ≤1.1 mmol/L might be the vigilant cutoff value. Conclusion: A lower serum Mg level was associated with higher all-cause mortality and cardiovascular mortality in patients receiving hemodialysis.